å¤åŠ¡æ‹‰é›…å›½ç«‹é«˜ä¸å››æ ¡äºŒå¹´çº§å¦ç”Ÿä½¿ç”¨ä»‹è¯â€œåœ¨â€çš„å›°éš¾åˆ†æž - Maulini, Nur; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractPreposition is one of the part of speech in Mandarin language. There are many preposition existed and some students are misused the